The portrayal of black women by Zimbabwean female playwrights: the case of in the continuum, who said i don’t want to dance and she no longer weeps - Sibanda, Khotso N. (Midlands State University, 2019)
This research investigates the portrayal of women by female Zimbabwean playwrights from different socio-historical backgrounds. The works that are analysed are Who said I don’t Want to Dance, by Thembelihle Moyo, Tsitsi Dangarembga’s She No Longer Weeps and Danai Gurira’s collaboration with Nikkole Salter in In the Continuum. Analysis of Salter’s female characters are presented in order to emphasise the universality of Black women’s experiences; and to highlight the distinctions between the Africans portrayed by Gurira with the African Americans portrayed by Salter. The study also explores the subject of feminism as a universally shared experience, but also how the plays in question expose the conclusive presence of intersectional feminism. In addition, African Womanist and African Feminist theoretical approaches as well as qualitative research methodology are utilised in analysing the presentation of the women in the three plays.